New insights into crosstalk between Nrf2 pathway and ferroptosis in lung disease - Yonghu Chen; Zhe Jiang; Xuezheng Li (Cell Death and Disease)
Abstract Ferroptosis is a distinctive process of cellular demise that is linked to amino acid metabolism, lipid oxidation, and iron oxidation. The ferroptosis cascade genes, which are closely associated with the onset of lung diseases, are among the regulatory targets of nuclear factor erythroid 2-related factor 2 (Nrf2). Although the regulation of ferroptosis is mostly mediated by Nrf2, the precise roles and underlying regulatory mechanisms of ferroptosis and Nrf2 in lung illness remain unclear. This review provides new insights from recent discoveries involving the modulation of Nrf2 and ferroptosis in a range of lung diseases. It also systematically describes regulatory mechanisms involving lipid peroxidation, intracellular antioxidant levels, ubiquitination of Nrf2, and expression of FSP1 and GPX4. Finally, it summarises active ingredients and drugs with potential for the treatment of lung diseases. With the overarching aim of expediting improvements in treatment, this review provides a reference for novel therapeutic mechanisms and offers suggestions for the development of new medications for a variety of lung disorders.